Stimulation of gastric glucagon secretion by epinephrine administration in dogs (Revista Española de Fisiología, 1990)
To determine the response of gastric A-cells to adrenergic substances, immunoreactive glucagon was determined simultaneously in the jugular vein and in the left gastroepiploic vein of totally depancreatized dogs. Under basal conditions a significant gradient of glucagon concentrations between the jugular and gastric veins was observed, whereas plasma insulin values were almost undetectable. Intravenous administration of epinephrine elicits a prompt and significant increase in glucagon concentrations in the gastric vein which persist during the time of hormone infusion. To ensure adequate adrenergic blockade, blockers were infused before epinephrine administration. Accordingly, after phentolamine, the infusion of epinephrine failed to increase gastric glucagon concentrations, while after propranolol, epinephrine induced a significant release of gastric glucagon. These results indicate that epinephrine stimulates gastric glucagon secretion and that this effect is mediated through alpha-adrenergic receptors.